AKHLAK MAZMUMAH: MEMAHAMI PERILAKU TERCELA DALAM ISLAM - Muspian Muspian (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Vicious character traits, known as akhlak mazmumah, refer to negative attributes that contradict Islamic teachings, such as arrogance, envy, hypocrisy, gossip, and lying. These behaviors not only damage an individual's relationship with Allah but also destroy social harmony. The cultivation of good character is essential in Islam, as it reflects the inner state of a person. The primary sources that guide the understanding of akhlak mazmumah are the Qur'an and the Hadith of Prophet Muhammad ﷺ, which explicitly forbid these harmful traits. The negative impact of akhlak mazmumah extends to the individual, society, and religion, leading to inner unrest, the destruction of social relationships, and the tarnishing of Islam's image. To avoid these undesirable traits, efforts such as self-reflection, repentance, seeking knowledge of good character, associating with righteous people, and practicing virtuous deeds are necessary. By improving one's character, a Muslim can achieve true happiness in both this world and the hereafter, while strengthening Islamic brotherhood.